ANALYSIS CORRELATION SOCIODEMOGRAPHICS ON THE LEVEL OF KNOWLEDGE AND ATTITUDE OF SOCIETY OF JAVA IN EFFORTS TO CONTROL THE COVID-19 OUTBREAKS - rizky meuthia pratiwi; Yodang .; Rahmad Yusuf; Nuridah -; Stefanus Mendes Kiik; Achmad Fauji; Hamka -; Yossi Fitriana (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2021)
Background: Corona Virus Disease-2019 (COVID-19) has been declared a pandemic throughout the world including in Indonesia, especially on the island of Java, with the number of cases always increasing, both confirmed cases and death cases. Objective: To find out the knowledge and attitudes of the people of Java Island related to sociodemographic (age, sex, education, and employment status) in efforts to control Covid-19. Methods: Cross-sectional design with a sample of 1,579 selected by simple random sampling. Collecting data using a questionnaire assisted by the google form program then the data is analyzed by using the chi-square test. Results: Of the 1,579 respondents who participated, namely the youth category by 57%, female gender by 76%, undergraduate education by 47.1%, and the work status of the student category by 41%. A total of 1008 respondents (64%) have good knowledge and 1251 respondents (79%) have a positive attitude. The results of the chi-square test on the knowledge variable showed that there was a relationship between age (p = 0.023) and education (p = 0.021), while gender (p = 0.359) and work status (p = 0.308) had no relationship. In the attitude variable, the results of the chi-square test showed that the p-value between age (p = 0.927), gender (p = 0.072), education (p = 0.140) and work status (p = 0.119) had no relationship, but the knowledge and attitude turns out that there is a value of p = 0.000 <0.05 with a confidence interval of 95%. These results indicate a relationship between knowledge and attitudes towards efforts to control COVID-19. Conclusion: The majority of people on the island of Java are knowledgeable and have a positive attitude in efforts to control COVID-19.